Homogenization design method for biomorphic composite materials - Hoppe, Ronald H.W.; Petrova, Svetozara (Journal of Computational Methods in Sciences and Engineering)
A structural optimization method based on the homogenization approach (the homogenization design method) has been applied to the modeling of the recently produced biomorphic composite materials. The design itself involves a structural optimization problem which is solved under a set of equality and inequality constraints on the state variables (displacements) and design parameters (lengths of the layers in the microstructure and angle of cell rotation). Primal-dual Newton-type interior-point method with proper optimality criteria is applied to the resulting nonconvex nonlinear optimization problem.
Keywords: biomorphic microcellular ceramics from wood; structural optimization; elasticity problems; homogenization technique; primal-dual interior-point methods